High proportion of pentazocine dependence among treatment-seeking female injecting drug users (FIDUs) in India: A distinct population?. (4th March 2018) - Ambekar, Atul; Parmar, Arpit; Mandal, Piyali; Therthani, Sumedha
ABSTRACT: Background. Adverse consequences of injecting are greater among female injecting drug users (FIDUs), yet treatment-seeking is low because of stigma, poor social support, and unavailability of gender-specific services. FIDUs, despite being a distinct subpopulation of women substance users, are sparsely studied. Aims. We aimed to study the sociodemographic and clinical profile of treatment-seeking FIDUs at a tertiary drug treatment center in North India. Methods. In this retrospective study, we reviewed medical records of all the FIDUs who sought outpatient treatment from January 1, 2011, to December 31, 2015. Results. Out of a total of 217 records of female patients, 44 were current IDUs (20.27%), with mean age 35.48 ± 10.13 years. Majority were Hindu (84.1%), married (81.8%), homemakers (52.3%) educated up to 12 years (65.9%). Primary drug of dependence was injection pentazocine for 33 patients (75.0%) and injection smack (street heroin) for 8 (18.2%). Commonest reason for initiation of drug use was iatrogenic ( n  = 25; 56.8%). Major physical complications were reported by 29 (65.9%), while 12 (22.8%) reported psychiatric comorbidity. Conclusion. A typical treatment-seeking FIDU is middle-aged, educated, homemaker using injecting pentazocine. High rate of injecting with iatrogenic onset highlights the need for women-specific services as well as awareness-building among physicians.